Sensing hydration and behavior of pyrene in POPC and POPC/cholesterol bilayers: A molecular dynamics study - Loura, Luís M. S. (2013)
Molecular dynamics (MD) simulations of bilayers of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) with varying amounts of cholesterol (0, 5, 20, and 40 mol%) were carried out in the absence and presence of inserted pyrene molecules. Both fluorophore and bilayer parameters were computed, for characterization of probe location and dynamics, as well as its effects on the host bilayer. In agreement with previous studies in fluid disordered bilayers, pyrene prefers to be located in the hydrophobic acyl chain region of POPC bilayers, close to the glycerol group of lipid molecules and causes ordering of the lipid acyl chains. However, incorporation of pyrene in binary POPC/cholesterol bilayers decreases the acyl chain order parameter (especially near the end of the chains), opposing the ordering effect of cholesterol. These effects are modest and mainly felt locally. Significantly, as the bilayer is enriched with cholesterol, the relative position of pyrene and the POPC carbonyl and phosphocholine groups is invariant, and the local water density around the probe decreases. This work clarifies and supports the cautious use of pyrene Ham effect to effectively measure equivalent polarity in lipid bilayers. Within the time scale of the MD simulations, which is of the magnitude of the fluorescence lifetime of pyrene, the thermally averaged polarity of lipid bilayers is nearly out of influence of spurious uncertainty in the transverse location of pyrene in the bilayers. This renders the values of equivalent polarity measurements through the pyrene Ham effect more reliable and reproducible than previously expected.